Comparative study on thermodynamics, combustion and emissions of turbocharged gasoline direct injection (GDI) engine under NEDC and steady-state conditions. (1st August 2018) - Liu, Qi; Fu, Jianqin; Zhu, Guohui; Li, Qingyu; Liu, Jingping; Duan, Xiongbo; Guo, Qiyi
Highlights: The thermodynamics, combustion and emissions of GDI engine under NEDC and steady-state conditions were compared. The ignition delay is mainly influenced by spark timing, then followed by other influence factors. The consistency of PMEP under NEDC and steady-state conditions is satisfactory. Both transient HC and CO emissions are larger than the steady-state values especially at low load. The transient NOx emission during NEDC is less than the steady-state level. Abstract: For a vehicle engine, it usually operates under transient conditions, and the transient behaviors represent its actual performance. In order to improve the actual performance of GDI engine during vehicle driving cycles, the vehicle test was conducted under new European driving cycle (NEDC), and the thermodynamics, combustion and emission characteristics were tested. Then, the transient performance of GDI engine was compared with the steady-state behaviors. In this way, the differences in various performance parameters under NEDC and steady-state conditions were demonstrated, and the reasons were revealed. Results show that, the spark timing, start of combustion (SOC), ignition delay, 50% combustion location and 10–90% combustion duration of GDI engine under NEDC deviate from their steady-state values seriously especially at low load, resulting in the large combustion instability. The consistency of pumping mean effective pressure (PMEP) under NEDC and steady-state conditions is satisfactory, while the indicated thermal efficiency has a large fluctuation during NEDC, and in most cases it is lower than the steady-state values. Both the transient HC and CO emissions are larger than the steady-state values especially at low load, while the transient NOx emission during NEDC is less than the steady-state values. All those not only demonstrated the change rules of combustion and emission characteristics of GDI engine under NEDC, but also provided guidance for improving the actual performance of vehicle engine.